Perceptions of gender equity and markers of achievement in a National Institute for Health Research Biomedical Research Centre: a qualitative study - Lorna R. Henderson; Rinita Dam; Syed Ghulam Sarwar Shah; Pavel V. Ovseiko; Vasiliki Kiparoglou (BMC, 2022)
Abstract Background The need to improve gender equity (GE) in academic medicine is well documented. Biomedical Research Centres (BRCs), partnerships between leading National Health Service (NHS) organizations and universities in England, conduct world-class translational research funded by the National Institute for Health and Care Research (NIHR). In 2011, eligibility for BRC funding was restricted to universities demonstrating sustained GE success recognized by the Athena SWAN Charter for Women in Science Silver awards. Despite this structural change, GE research in BRC settings is underdeveloped, yet critical to the acceleration of women's advancement and leadership. To explore both women's and men's perceptions of GE and current markers of achievement in a BRC setting. Methods Thematic analysis of data from two research projects: 53 GE survey respondents' free-text comments (34 women, 16 men), and 16 semi-structured interviews with women affiliated to the NIHR Oxford BRC. Results Four major themes emerged from the analysis: perceptions of the Athena SWAN Charter for Women in Science (GE policy); views on monitoring GE in BRCs; views on current markers of achievement in academia and GE; and recommendations for actions to improve GE in BRC settings. Monitoring of GE in BRCs was deemed to be important, but complex. Participants felt that current markers of achievement were not equitable to women, as they did not take contextual factors into account such as maternity leave and caring responsibilities. BRC-specific organizational policies and metrics are needed in order to monitor and catalyse GE. Conclusions Markers of achievement for monitoring GE in BRCs should consider contextual factors specific to BRCs and women's career progression and professional advancement. GE markers of achievement should be complemented with broader aspects of equality, diversity and inclusion.